State-of-the-art on monolingual lexicography for Denmark (Danish) - Lars Trap-Jensen (Slovenščina 2.0: Empirične, aplikativne in interdisciplinarne raziskave, 2019)
This minireview provides an overview of the lexicographic situation in Denmark, introducing the most important dictionary works. The major historical dictionaries are mentioned but the main focus is on contemporary lexicography and the companies and institutions currently active in the field. In particular, it is noted whether dictionaries are digitally available and if they are subject to regular updating.